2003
DOI: 10.1139/x03-119
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fertilization, weed control, and pine litter on loblolly pine growth and productivity and understory plant development through 12 growing seasons

Abstract: On a silt loam soil in central Louisiana, three cultural treatments were applied to a seedling loblolly pine (Pinus taeda L.) plantation. The treatments were in a 2 × 2 × 2 factorial design: (1) no fertilization or a broadcast application of 177 kg N/ha and 151 kg P/ha; (2) no herbicides applied or broadcast or spot applications of hexazinone, sulfometuron methyl, or glyphosate herbicides and felling as required to control competing vegetation during the first three growing seasons; and (3) no litter applied o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 25 publications
4
16
1
Order By: Relevance
“…Haywood et al 2003;Jylhä and Hytönen 2006). Observations in the weeks following herbicide application in the current study indicated some pine-needle necrosis on lower branches.…”
Section: Discussionsupporting
confidence: 48%
“…Haywood et al 2003;Jylhä and Hytönen 2006). Observations in the weeks following herbicide application in the current study indicated some pine-needle necrosis on lower branches.…”
Section: Discussionsupporting
confidence: 48%
“…Stem production in our study compared favorably with other intensively managed loblolly pine studies of similar age in the southeastern United States (Table 7). Increased fertilization rates (Samuelson et al 2004;Allen et al 2005a) or greater stocking levels (Haywood et al 1997;Adegbidi et al 2002Adegbidi et al , 2005Allen et al 2005a) may be reasons why other studies showed greater stem production rates. Production and volume accumulation are expected to continue increasing until intertree competition exceeds a basal area threshold of 25 m2.ha-I .…”
mentioning
confidence: 97%
“…That lowintensity burning has the potential to stimulate the growth of vegetation, particularly some woody species, has been recorded [1,16,23,31]. Conversely, retaining the post-harvest residues as an organic mulch on the site has been shown to reduce the rate of growth of competitive vegetation [4,8,12,16]. Schumann et al [26] demonstrated that post-harvest residues act as a physical and chemical barrier, reducing the rate of seed germination thereby delaying the onset of inter-specific competition.…”
Section: Discussionmentioning
confidence: 99%